Estimulação do desenvolvimento neuropsicomotor de crianças com síndrome congênita do zika vírus - Junqueira, Cora Coralina dos Santos (2019)
Introduction: Children with Congenital Zika Virus Syndrome has severe neuropsychomotor impairment, requiring continuous monitoring by professionals for an effective neurostimulation in order to achieve a better quality of life. Thus, the family plays a fundamental role in this process, using the home environment to provide stimuli to these children. Objective: To analyze the neuropsychomotor stimulation of children with congenital Zika virus syndrome, according to women caregivers and health professionals. Methodology: This is a qualitative, descriptive and exploratory research, conducted with ten women caregivers of children with Congenital Zika Virus Syndrome and five professionals who work in a referral service in a city in Pernambuco, Brazil. Data collection took place between November 2018 and March 2019, using semi-structured interviews. The empirical material was submitted to thematic analysis. The project was approved by the Research Ethics Committee, protocol number 3.426.153 and CAAE: 00452618.8.0000.5188. Results: The caregivers play a daily struggle in search of answers and better living conditions for the uncertain future of these children, with experience permeated by fear, insecurity and lack of support, which compromises the child's stimulation at home. Professionals recognize the situation, however, emphasize the importance of continuing the stimulus to preserve neurological and psychomotor abilities of these children. Conclusion: It is essential the support of health professionals to these women caregivers, seeking to reframe their lives, welcoming them and knowing the uniqueness of each family, so that they can be able to stimulate children. More effective public policies are also needed to meet the real needs of children with Zika virus congenital syndrome and their families.